Evaluation of lung volumes, vital capacity and respiratory muscle strength after cervical, thoracic and lumbar spinal surgery - Oliveira, Marcio Aparecido; Vidotto, Milena Carlos; Nascimento, Oliver Augusto; Almeida, Renato; Santoro, Ilka Lopes; Sperandio, Evandro Fornias; Jardim, José Roberto; Gazzotti, Mariana Rodrigues (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: Studies have shown that physiopathological changes to the respiratory sys-tem can occur following thoracic and abdominal surgery. Laminectomy is considered to be a peripheral surgical procedure, but it is possible that thoracic spinal surgery exerts a greater influence on lung func-tion. The aim of this study was to evaluate the pulmonary volumes and maximum respiratory pressures of patients undergoing cervical, thoracic or lumbar spinal surgery. DESIGN AND SETTING: Prospective study in a tertiary-level university hospital. METHODS: Sixty-three patients undergoing laminectomy due to diagnoses of tumors or herniated discs were evaluated. Vital capacity, tidal volume, minute ventilation and maximum respiratory pressures were evaluated preoperatively and on the first and second postoperative days. Possible associations between the respiratory variables and the duration of the operation, surgical diagnosis and smoking status were investigated. RESULTS: Vital capacity and maximum inspiratory pressure presented reductions on the first postopera-tive day (20.9% and 91.6%, respectively) for thoracic surgery (P = 0.01), and maximum expiratory pressure showed reductions on the first postoperative day in cervical surgery patients (15.3%; P = 0.004). The inci-dence of pulmonary complications was 3.6%. CONCLUSIONS: There were reductions in vital capacity and maximum respiratory pressures during the postoperative period in patients undergoing laminectomy. Surgery in the thoracic region was associated with greater reductions in vital capacity and maximum inspiratory pressure, compared with cervical and lumbar surgery. Thus, surgical manipulation of the thoracic region appears to have more influence on pulmonary function and respiratory muscle action.